Evaluasi Proses Amendemen Undang-Undang Dasar Tahun 1945: Perspektif Habermasian - Costantinus Fatlolon (Jurnal Konstitusi, 2022)
This article evaluates the amendment process of the 1945 Constitution conducted by the MPR from 1999 to 2002. The theoretical framework used is Jürgen Habermas’s theory of law and democracy. By employing an expositive-critical-reconstructive approach, this article argues the amendment of the 1945 Constitution was inclusive but not participatory because the process was more dominated by the MPR and it did not include the active participation of ordinary citizens, including civil society groups, the mass media, and radical groups in the society. The remedy to this problem is for the MPR to institutionalize ideal conditions of deliberative democracy that grant publicity, transparency, civic participation, and rational communication between the executive body and citizens in every phase of the constitutional amendment process.